Molecular Determinants of Head and Neck Cancer (Current Cancer Research,, 2018)
Squamous cell cancers of the head and neck (SCCHN), also known as head and neck cancers (HNC) encompass malignancies of the oral cavity, larynx, nasopharynx and pharynx, and are diagnosed in over 500,000 patients worldwide each year, accounting for 5% of all malignancies. It is estimated that approximately 50,000 patients develop head and neck cancer annually in the United States, of whom approximately 50% succumb to this cancer. For most cases of SCCHN, treatment is multimodal, often combining surgery or irradiation with chemotherapy; even successfully treated patients frequently experience durable and severe side effects. Improving cure rates and reducing chronic morbidity are urgent clinical needs for head and neck cancer. However, in contrast to cancer types such as breast or prostate that have been much studied and have well-defined biology, until recently, relatively few researchers investigated the molecular basis of HNC, making it difficult to design targeted treatments with better efficacy and less debilitating side effects. This volume will provide an overview of the factors contributing to disease pathogenesis, including the recognition of discrete molecular subtypes with distinct etiology, prognosis, and treatment response. This volume will familiarize the reader with the critical signaling pathways and oncogenic drivers for HNC. It will outline the differences between HPV-positive and HPV-negative disease, and how these differences affect treatment choice and outcome. The book will emphasize developments in the past five years, including the growing understanding of the genomic and epigenomic features of the disease based on analysis of next generation sequencing (NGS) data, and timely topics such as the analysis of HNC stem cell populations, non-coding mRNAs, and inflammatory response. It will address exciting new therapeutic approaches such as the use of immunotherapies to treat HNC patients. Overall, the book will provide the reader with current understanding of the biology and treatment of the disease, and describe timely questions that will guide future research aimed at controlling and curing this disease.